Proses Penerbitan Sertifikat Hak Atas Tanah Melalui Konversi Pada Kantor Pertanahan - Andi Heridah; Aksah Kasim (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2022)
This study aims to determine the process of issuing land rights certificates through conversion at the Land Office in Parepare City. This study uses a normative juridical approach. A juridical approach is used to analyze various principles and theories related to the problems studied. The results showed that the implementation of the issuance of land rights certificates through the conversion process still refers to Government Regulation no. 24 of 1997 so in the process of issuing land rights certificates through the conversion process at the Parepare City Land Office, there was also no change. The factors that hinder the process of issuing land rights certificates through conversion are the level of community knowledge is still low; lack of technical implementing personnel; lack of facilities and infrastructure, and incomplete administration of requirements for certificate makers.